Caracterização morfológica, fisiológica e bioquímica da Corticeira-do-banhado em condições de alagamento - Larré, Cristina Ferreira (2011)
The Erythrina crista-galli L., popularly known as corticeira-do-banhado, is a medium sized tree belonging to family Fabaceae, known especially for their vibrant colored flowers. The cork is listed as a plant immune to the court, by CONAMA, such is the devastation of their habitat and due to its importance in the restoration of riparian vegetation and restoration of degraded ecosystems in areas with periodic flooding in a short duration. Therefore, the objective was to study the morphological, physiological and biochemical alterations in corticeirado-banhado in response to stress caused by the difference in water conditions. Plants derived from seeds were grown in 0.5 liter pots in a greenhouse and transferred to five liters pots. We used two treatments: root plants flooded with maintaining a water level above the ground and plants are not flooded (control), maintained at field capacity. We evaluated growth parameters, changes in photosynthetic apparatus by analyzing the fluorescence of chlorophyll a and transient activity of enzymes of oxidative stress, lipid peroxidation and quantification of hydrogen peroxide in leaves and roots but the activity of fermentative enzymes in roots. The experimental design was randomized blocks and the results were submitted to analysis of variance (ANOVA) and analyzed by comparison of means by Tukey test at 5% significance. The results revealed that the flooding during the period studied, does not compromise the plants Corticeira-do-banhado, because they continued to develop even under flooding, although with significantly lower growth compared to plants not flooded. Plants are also able to trigger the enzymatic antioxidant defense system, thereby reducing oxidative damage. Likewise, the species is able to use the route as an alternative fermentation to maintain energy production during the hypoxic condition. The formation of adventitious roots is the most obvious morphological strategy for the survival of plants under flooding, allowing them to occur through a metabolic slow and continuous adjustment throughout the period of stress.